Fabrication of Stable Dye Sensitized Solar Cell with Gel electrolytes Using Poly(ethylene oxide)-Poly(ethylene glycol). (10th September 2015) - Anantharaj, G.; Joseph, James; Selvaraj, M.; Jeyakumar, D.
Abstract: Fabrication of quasi solid state dye sensitized solar cell with a stable gel electrolyte employing poly(ethylene oxide) (PEO)-poly(ethylene glycol) (PEG) is reported in this paper. PEO-PEG with either one of alkali iodides (LiI or NaI or KI), 1, 2-dimethyl-3-propyl imidazolium iodide (DMPI), 4-tertbutylpyridine (TBP) and iodine in acetonitrile were used for the gel electrolyte preparation. The ionic conductivity and the triiodide diffusion coefficient of the gel electrolytes were measured by Electrochemical Impedance Spectroscopy. The photoconversion efficiency of gel state DSSC with NaI was found to be 5.4% at 100 mW/cm 2 with AM 1.5 Gfilter. When nanocrystalline TiO2 was used as the filler in the gel electrolyte, the photoconversion efficiency was found to be increased up to 6.3%. The quasi solid state DSSC retained its initial value for 600 hours aging under ambient conditions.